OMNI: Open Mind Neuromodulation Interface for accelerated research and discovery - Roarr, BN; Perrone, RS; Jamshed, F; Gilron, R; Denison, TJ; Starr, PA; Herron, JA; Borton, DA; Ieee (Institute of Electrical and Electronics Engineers, 2021)
Electrical neuromodulation is an approved therapy for a number of neurologic disease states, including Parkinson's disease (PD), Obsessive Compulsive Disorder, Essential Tremor, epilepsy and neuropathic pain. Neuromodulatory strategies are also being piloted for an increasing number of additional indications, including Major Depressive Disorder, Dystonia, and addiction. The development of implantable devices capable of both neural sensing and adaptive stimulation may prove essential for both improving therapeutic outcomes and expanding the neuromodulation indication space. Nevertheless, an increasingly fragmented device ecosystem forces researchers and therapy developers to customize and reinvent data visualization, clinician engagement, and device control software to support individual clinical studies. Each hardware platform provides a unique software interface to the implanted neurostimulator, making pre-existing code from prior studies difficult to leverage for future work - a hindrance that will expand as device technology diversifies. Here, we envision, detail, and demonstrate the use of a novel software architecture, OMNI, that accelerates neuromodulation research by providing a flexible, platform- and device-agnostic interface for clinical research and therapy development.